The Christian God - Swinburne, Richard (New York : Oxford , Clarendon Press., 1994)
"What is it for there to be a God, and what reason is there for supposing him to be the Traditional Christian God? In this pivotal volume of his tetralogy, Richard Swinburne builds a rigorous metaphysical system for describing the world, and applies this to assessing the worth of the Christian tenets of the Trinity and the Incarnation." "Part I is dedicated to analysing the categories needed to address accounts of the divine nature - these are substance, cause, time, and necessity. Part II begins by setting out, in terms of these categories, the fundamental doctrine of Western religions - that there is a God. After pointing out some of the different ways in which this doctrine can be developed, Swinburne spells out the simplest possible account of divine nature." "He then goes on to clarify the implications of this account for the specifically Christian doctrines of the Trinity (that God is 'three persons in one substance') and of the Incarnation (that God became incarnate in Jesus Christ). Swinburne finds that there are good reasons to believe the Christian additions to the core Western idea of God." "The Christian God builds upon Swinburne's acclaimed previous work to form a self-contained text which will no doubt become a classic in the philosophy of religion."--Jacket
Part 1: Metaphysics ; Substances -- Thisness -- Causation -- Time -- Necessity -- Part 2: Theology ; The Divine properties -- The Divine nature -- The Trinity -- The possibility of incarnation -- The evidence of Incarnation
Includes bibliographical references (pages 239-253) and index
Keywords: God (Christianity); Trinity; Incarnation; Christianity -- Doctrines -- God